Comparison of Clinical Presentation and Per-operative Findings of Laparoscopic Assisted Vaginal Hysterectomy - Shamima, Mosammad Tanbir Nahar; Begum, Fatema; Begum, Sheuly; Rahman, Ahsan Habibur; Karmaker, Anuradha; Biswas, Partha Protim (Journal of Current and Advance Medical Research, 2022)
Background: Laparoscopically assisted vaginal hysterectomy can be very useful surgery. Objective: The purpose of the present study was to evaluate the clinical diagnoses and preoperative findings with their histopathological results due to hysterectomy. Methodology: This was a retrospective Observational study carried out Department of Obstetrics and Gynaecology at Sir Salimullah Medical College & Mitford Hospital (SSMC & MH), Dhaka, Bangladesh. Patients requiring of laparoscopic assisted vaginal hysterectomy, admitted in the Department of Obstetrics and Gynaecology, SSMC & MH, Dhaka. The patients having of laparoscopic assisted vaginal hysterectomy were interviewed, clinical examination was done and per operative findings and histopathological reports were recorded accordingly. Results: The commonest indication for laparoscopic assisted vaginal hysterectomy in the series is leiomyoma uterus (26%) and dysfunctional uterine bleeding is the second most common (24.0%) indication. Commonest complaint of the patients suffering from dysfunctional uterine bleeding (DUB) was irregular bleeding. Among the 12 cases of clinically diagnosed DUB. About 11 cases had no apparent organic lesion and 10 cases were confirmed by histopathological examination to have no organic lesion. Peroperative findings were similar to clinical diagnosis in 88.0% cases and histopathological findings were similar to clinical diagnosis in 82.0% cases. Conclusion: Clinical diagnoses in hysterectomy patients are mostly consisted with the per-operative findings and also with the histopathological findings. Journal of Current and Advance Medical Research, January 2022;9(1):26-31